Pre- and post-accident environmental transfer of radionuclides in Japan: lessons learned in the IAEA MODARIA II programme. (1st June 2022) - Tagami, Keiko; Hashimoto, Shoji; Kusakabe, Masashi; Onda, Yuichi; Howard, Brenda; Fesenko, Sergey; Pröhl, Gerhard; Harbottle, Andra-Rada; Ulanowski, Alexander
Abstract: An international review of radioecological data derived after the accident at the Fukushima Daiichi nuclear power plant was an important component of activities in working group 4 of the IAEA Models and data for radiological impact assessment, phase II (MODARIA II) programme. Japanese and international scientists reviewed radioecological data in the terrestrial and aquatic environments in Japan reported both before and after the accident. The environmental transfer processes considered included: (a) interception and retention radionuclides by plants, (b) loss of radionuclides from plant and systemic transport of radionuclides in plants (translocation), (c) behaviour of radiocaesium in soil, (d) uptake of radionuclides from soil by agricultural crops and wild plants, (e) transfer of radionuclides from feedstuffs to domestic and wild animals, (f) behaviour of radiocaesium in forest trees and forest systems, (g) behaviour of radiocaesium in freshwater systems, coastal areas and in the ocean, (h) transport of radiocaesium from catchments through rivers, streams and lakes to the ocean, (i) uptake of radiocaesium by aquatic organisms, and (j) modification of radionuclide concentrations in food products during food processing and culinary preparation. These data were compared with relevant global data within IAEA TECDOC-1927 'Environmental transfer of radionuclides in Japan following the accident at the Fukushima Daiichi Nuclear Power Plant'. This paper summarises the outcomes of the data collation and analysis within MODARIA II work group 4 and compares the Japan-specific data with existing radioecological knowledge acquired from past and contemporary radioecological studies. The key radioecological lessons learned are outlined and discussed.